1980
DOI: 10.1111/j.1432-1033.1980.tb04424.x
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Sea‐Urchin‐Sperm Histone φ1 (H1) in Chromatin and in Free Solution

Abstract: The lysine-rich H1-type histone 41 from the sperm of the sea urchin Arbaciu lixula has been subjected to tryptic digestion in free solution at high ionic strength. Tw trypsin-resistant peptides G41 and LG41 have been isolated, comprising 81 and 93 amino acids respectively, i.e. about a third of the intact histone. Circular dichroism and 270-MHz proton NMR have been used to demonstrate that the smaller peptide G41 contains all the secondary and tertiary structure of intact histone 41. It is concluded that the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1981
1981
1984
1984

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…We used two proteases to test in vitro a functional correlation with the asymmetry observed in the sequence. Trypsin has provided information about the structure of chromatin proteins, both core histones (Weintraub, 1975;Whitlock and Simpson, 1977) and histone HI (Hartman et al, 1977) and related proteins (Aviles et al, 1978;Puigdomenech et al, 1980). This enzyme has been used to test the domain hypothesis for HMG-1, -2 and -E (Paulau et al, 1980;Reeck et al, 1982;Cary et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used two proteases to test in vitro a functional correlation with the asymmetry observed in the sequence. Trypsin has provided information about the structure of chromatin proteins, both core histones (Weintraub, 1975;Whitlock and Simpson, 1977) and histone HI (Hartman et al, 1977) and related proteins (Aviles et al, 1978;Puigdomenech et al, 1980). This enzyme has been used to test the domain hypothesis for HMG-1, -2 and -E (Paulau et al, 1980;Reeck et al, 1982;Cary et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…We have examined the domain structure for HMG-1 and -2 from calf thymus following a strategy similar to that used to show the domain structure of histone HI (Hartman et al, 1977;Aviles et al, 1978;Puigdomenech et al, 1980). The proteins were digested with proteases and the products of the digestion analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…The physical characterization described above indicates that both the secondary structure and tertiary structure of S. granularis histone H1 are very similar to those of A. lixula histone HI, despite significant compositional differences. The folding domain of H1 histones in which the secondary and tertiary structures are located is of approximately 80 residues (Hartman et al, 1977;Puigdomenech et al, 1980;Allan et al, 1980) and is centrally located. Preliminary digestion studies indicate that S. granularis histone H 1 also contains a trypsinresistant domain of molecular weight approx.…”
Section: Discussionmentioning
confidence: 99%
“…86 residues in calf thymus HI) and a long unstructured C-terminal domain of very basic composition comprising almost half the molecule (approx. 93 residues in calf thymus HI) (Chapman et al, 1976;Hartman et al, 1977;Puigdomenech et al, 1980;Barbero et al, 1980;Aviles et al, 1978). By reconstituting several HI peptides on to chromatin depleted of its original Hi, it was shown that the central globular domain alone is able to close two full turns of nucleosomal DNA.…”
mentioning
confidence: 99%